Idiopathic gross dilatation of the pancreatic duct with exocrine insufficiency in a patient with type 1 neurofibromatosis. (March 2022) - Jayarajah, Umesh; Basnayake, Oshan; Wijerathne, Pradeep Kumara; Fernandopulle, Nilesh; Sivaganesh, Sivasuriya
Pancreatic duct dilatation occurs in conditions including chronic pancreatitis, pancreatic carcinoma and intraductal papillary mucinous neoplasms. Although several pancreatic benign and malignant tumours have been reported in association with type 1 neurofibromatosis, an association with gross pancreatic duct dilatation or ectasia has not been previously published. We report on a patient with type 1 neurofibromatosis found to have idiopathic gross pancreatic duct dilatation and exocrine insufficiency. A 51-year-old female with type 1 neurofibromatosis presented with weight loss and steatorrhoea. Computed tomography and magnetic resonance cholangiopancreatography showed a possible cystic lesion in the head of the pancreas, a grossly dilated main pancreatic duct and minimal thinned out pancreatic parenchyma. Endosonography confirmed diffuse dilatation of the pancreatic duct with no evidence of a separate cystic neoplasm. Endosonography-guided aspiration revealed non-mucinous, clear fluid with high amylase and normal carcinoembryonic antigen levels. The patient was prescribed pancreatic enzyme supplementation and showed symptomatic improvement. Associations between type 1 neurofibromatosis and pancreatic duct ectasia or chronic pancreatitis have not been reported, and this finding may be coincidental. Clinical presentation in conjunction with multimodal imaging and biochemical and cytological fluid analysis did not reveal the aetiology of the ectatic duct system and attenuated glandular tissue in this patient which is most likely congenital.